Systems of low-frequency tapping with the use of a stimulant in rubber plantations in Mato Grosso State - Rondon E V; Abreu J G DE; Santos A M DOS; Silva D DA; Souza C A F DE; Vital A R (Pesquisa Agropecuaria Brasileira, 1997)
In trials from September 1989 to December 1993, trees in 8-year-old stands of rubber clones IAN 873 and IAN 717 at 2 sites in Mato Grosso, Brazil were tapped on virgin bark 1.5 m above ground level at intervals of 2, 3, 4 or 7 days and were treated with the stimulant Ethrel [ethephon] at 2.5;at a rate of 1 ml solution/tree, 4, 6, 8 or 10 times annually, 3 days before tapping. Tapping at intervals of 4 or 7 days and stimulation 10 times/year gave the highest latex yields. Although IAN 717 was more prone to drying-out of the panel of bark, this clone produced significantly more dry rubber (1.29 t/ha per year) than clone IAB 873 (0.58 t) under the same conditions of production.
Source Year: 1997
Keywords: Low-frequency tapping; Mato Grosso; Rubber plantation